Adaptation of consumer law to the digital age: EU Directive 2019/2161 on modernisation and better enforcement of consumer law - Đurović Mateja (Anali Pravnog Fakulteta u Beogradu)
This Paper examines the most important innovations in the recently adopted European Directive 2019/2161 on better enforcement and modernisation of Union consumer protection rules. First, by adding the innovative rules, such as the ones on the trustworthiness of online reviews, the Directive aims to adapt the European regulatory framework on consumer protection to the challenges and particularities of the digital age and the digital market. Second, through the sharp rise of the fines for breach of consumer law and through the introduction of a mandatory individual remedy to the consumers who has been a victim of unfair commercial practices, the Directive substantially contributes to strengthening of the general enforcement mechanism of EU consumer law and achievement of high level of consumer protection.